Eight years since the Mexico-Uruguay FTA. An evaluation - Morales, María Esther; Almonte, Leobardo; Carbajal, Yolanda (Estudios Internacionales, 2012)
The Free Trade Agreement between Mexico and Uruguay, in operation since 2004, has led to a remarkable increase of bilateral commercial exchange. This document evaluates the results of this Agreement for both countries, since it entered into force, with particular reference to commercial exchange. Mexican exports to Uruguay consist mainly of manufactured products of medium and high technology, while the South American economy provides raw materials and manufactured products based on raw materials and medium technology. It is concluded that trade has been more favourable to Uruguay.